Social determinants of health impact on cancer affecting children, adolescents, and young adults: systematic review and meta-analysis - Sharara, Muhannad; Tjioe, Kellen Cristine; Miranda-Galvis, Marisol; Santellano Juarez, Brenda; Agrawal, Gagan; Balas, E. Andrew; Johnson, Theodore S.; Cortes, Jorge E. (Frontiers in Adolescent Medicine, 2024)
To analyze the impact of social determinants of health (SDH) on cancer outcomes of children and adolescents and young adults (AYA) treated for cancer.The protocol for this study was registered at PROSPERO (CRD402022346854). A search strategy was implemented across six databases over the last two decades. The focus narrowed to 31 studies conducted in the United States, involving patients between the ages of 15 and 39, assessing survival outcomes based on SDH factors. The Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Analytical Cross-Sectional Studies was employed for risk of bias assessment.The most extensively examined SDH factors were neighborhood socioeconomic status (nSES) and health insurance status. Other variables investigated were location of care (6/31), poverty level (5/31), education level (3/31), marital status (4/31), median income (3/31), travel distance to medical facility (3/31), language isolation (2/31), and unemployment (1/31). The primary outcome evaluated was overall survival (OS) and cancer-specific survival (CSS). Meta-analyses focusing on hematological malignancies revealed statistically significant associations, such as lowest nSES correlating with worse OS (hazard ratio [HR]:1.46, 95%-CI:1.29-1.66) and CSS (HR:1.43, 95%-CI:1.20-1.72), Medicaid/public insurance linked to worse OS (HR: 1.21, 95%-CI:1.16-1.26), and no insurance associated with worse OS (HR:1.35, 95%-CI:1.17-1.55).The study highlights the fragmented and incomplete nature of research on SDH in cancer treatment in this age group. Health insurance coverage and nSES were the most studied, revealing significant impacts on patient survival. Identifying vulnerable Deleted: under 40 years Deleted: patients through such analyses could inform policy decisions and address existing gaps in SDH research more effectively.